Phenotypic features of cancer cachexia‐related loss of skeletal muscle mass and function: lessons from human and animal studies. Issue 2 (30th March 2021) - Martin, Agnès; Freyssenet, Damien
Abstract: Cancer cachexia is a complex multi‐organ catabolic syndrome that reduces mobility, increases fatigue, decreases the efficiency of therapeutic strategies, diminishes the quality of life, and increases the mortality of cancer patients. This review provides an exhaustive and comprehensive analysis of cancer cachexia‐related phenotypic changes in skeletal muscle at both the cellular and subcellular levels in human cancer patients, as well as in animal models of cancer cachexia. Cancer cachexia is characterized by a major decrease in skeletal muscle mass in human and animals that depends on the severity of the disease/model and the localization of the tumour. It affects both type 1 and type 2 muscle fibres, even if some animal studies suggest that type 2 muscle fibres would be more prone to atrophy. Animal studies indicate an impairment in mitochondrial oxidative metabolism resulting from a decrease in mitochondrial content, an alteration in mitochondria morphology, and a reduction in mitochondrial metabolic fluxes. Immuno‐histological analyses in human and animal models also suggest that a faulty mechanism of skeletal muscle repair would contribute to muscle mass loss. An increase in collagen deposit, an accumulation of fat depot outside and inside the muscle fibre, and a disrupted contractile machinery structure are also phenotypic features that have been consistently reported in cachectic skeletal muscle. Muscle function is also profoundly altered during cancer cachexia with a strong reduction in skeletal muscle force. Even though the loss of skeletal muscle mass largely contributes to the loss of muscle function, other factors such as muscle–nerve interaction and calcium handling are probably involved in the decrease in muscle force. Longitudinal analyses of skeletal muscle mass by imaging technics and skeletal muscle force in cancer patients, but also in animal models of cancer cachexia, are necessary to determine the respective kinetics and functional involvements of these factors. Our analysis also emphasizes that measuring skeletal muscle force through standardized tests could provide a simple and robust mean to early diagnose cachexia in cancer patients. That would be of great benefit to cancer patient's quality of life and health care systems.